17β-Estradiol (E2) Upregulates the ERα/SIRT1/PGC-1α Signaling Pathway and Protects Mitochondrial Function to Prevent Bilateral Oophorectomy (OVX)-Induced Nonalcoholic Fatty Liver Disease (NAFLD) - Ying Tian; Xinyu Hong; Yuan Xie; Zaixin Guo; Qi Yu (MDPI AG, 2023)
Premature menopause is associated with an increased prevalence of nonalcoholic fatty liver disease (NAFLD). Menopausal hormone therapy (MHT) has been widely used in clinical practice and has the potential to protect mitochondrial function and alleviate NAFLD. After bilateral oophorectomy (OVX), female rats without 17β-estradiol (E2) intervention developed NAFLD, whereas E2 supplementation was effective in preventing NAFLD in female rats. The altered pathways and cellular events from both comparison pairs, namely, the OVX vs. sham group and the OVX vs. E2 group, were assessed using transcriptomic analysis. KEGG pathways enriched by both transcriptomic and metabolomic analyses strongly suggest that oxidative phosphorylation is a vital pathway that changes during the development of NAFLD and remains unchanged when E2 is applied. Liver tissue from the OVX-induced NAFLD group exhibited increased lipid peroxidation, impaired mitochondria, and downregulated ERα/SIRT1/PGC-1α expression. An in vitro study indicated that the protective effect of E2 treatment on hepatic steatosis could be abolished when ERα or SIRT1 was selectively inhibited. This damage was accompanied by reduced mitochondrial complex activity and increased lipid peroxidation. The current research indicates that E2 upregulates the ERα/SIRT1/PGC-1α signaling pathway and protects mitochondrial function to prevent OVX-induced NAFLD.